Evaluation of Professional Competence of School Principals in the USA - Dehtiarova, O. (Problems of Engineer-Pedagogical Education, 2018)
In the article the problem of qualitative recruitment and development of head teachers in the USA has been explored, special attention has been paid to the fact that the current events in society and their impact on education are reflected in the role, recruitment and development of school principals, because of which the role of school principals is changing. The article raises the problem of the effective management of an educational institution and decentralization of management at the institution level, delegation of authority. The paper analyzes approaches to assessing professional competence of school principals, considering the example of Minnesota, and to measuring the professional competence of an independent nonprofit organization (using the example of Kentucky). Attention is focused on the process of assessing professional competence, the evaluation algorithm and one of the evaluation tools – professional testing. The 12 core competencies (С-12) that were identified as critical for the successful performance by the person of their duties in the light of the management of education were highlighted and analyzed. Conclusions regarding the feasibility of developing a model for evaluating professional competence of heads of institutions of general secondary education are made.